A tradição Juremeira e suas relações com os rituais de candoblé e umbanda na casa Ilê Axé Xangô Agodô. - Melo, Rodrigo da Silva (2013)
The present work is a study of case. The objective is to investigate through the ethnomusicological stand point, the relations among the cult of jurema with the candomblé and umbanda, into the rituals of the house Ilê Axé Xangô Agodô. The house is located in João Pessoa City, in state of Paraíba, during eighteen years. There, are worshiped entities of jurema and the orishas, from candomblé. The cult of two different entities in the same house connotes the influence of umbanda, associated with the movement of federalization of the Afro-Brazilian cults in the country. From the bibliography, are present the individual characteristics of the three cults and the beginning of the interaction among them. This perspective provides the basis to understand the elements that constitute the house in focus. Therefore, it was drawn up an overview that presents the norms, acceptations, and directives of the house, apprehended through interaction with the members of the cult. Their ceremonies are described to demonstrate the format of the cults and the doctrinaire acceptations. Music is an important element in the constitution of these ceremonies, it is directly bind to its structure, and is present in all the rituals. The analysis of this element expands the possibilities to understand the dimensions of reworkings in the cult of jurema starting from its intersection with the candomblé and umbanda.